Access to Justice for Persons with Disabilities as Victims of Sexual : Fulfilment of Reasonable Accommodation in Judicial Process - Wahyudi, Abdullah; Fathan; Kasiyati, Siti (PLD UIN Sunan Kalijaga, 2023)
Examinations of cases involving persons with disabilities are often stopped halfway due to the non-fulfillment of reasonable accommodation by law enforcement officials. This study aims to determine the fulfillment of reasonable accommodation for persons with disabilities in the judicial process and the obstacles faced in the judicial process. This research is non-doctrinal research with the object of research in handling cases of persons with disabilities as victims of crime in the judicial process. Research on the fulfillment of adequate accommodation for persons with disabilities in the judicial process has never been conducted. This research is expected to provide improvements in the fulfillment of decent accommodation for persons with disabilities. The result of this study is that some accommodations are feasible to fulfil and others are not met and obstacles are found in the fulfillment of decent accommodation. Pemeriksaan perkara-perkara yang melibatkan penyandang disabilitas sering terhenti di tengah jalan karena tidak dipenuhinya akomodasi yang layak oleh aparat penegak hukum. Penelitian ini bertujuan untuk mengetahui pemenuhan akomodasi yang layak bagi penyandang disabilitas dalam proses peradilan dan hambatan-hambatan yang dihadapi dalam proses peradilan. Penelitian ini adalah penelitian non-doktrinal dengan objek penelitian berupa penanganan kasus-kasus penyandang disabilitas sebagai korban tindak pidana dalam proses peradilan. Penelitian tentang pemenuhan akomodasi yang layak bagi penyandang disabilitas dalam proses peradilan belum pernah dilakukan. Penelitian ini diharapkan dapat memberikan perbaikan dalam pemenuhan akomodasi yang layak bagi penyandang disabilitas. Hasil penelitian ini adalah sebagian akomodasi yang layak terpenuhi dan sebagia lainnya tidak dipenuhi dan ditemukan hambatan-hambatan dalam pemenuhan akomodasi yang layak.